GEOCHEMICAL GRANITOID’S PERCULARITIES OF DIFFERENT PRECAMBRIAN STAGES OF TECTONIC-MAGMATIC ACTIVIZATION ON UKRAINIAN SHIELD - KOSTENKO, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On geochemical features of granitoids the complexes of the Ukrainian shield are determined, which one immediately were formed owing to development of processes tectonic-magmatical activating or were subject to their influencing. The stages of granitoid's tectonic-magmatical activating of the Ukrainian shield are chosen and are confirmed also by datas of a dating by radioactivity. The temporary boundaries of stages will be clocked with applicable geochemical and metallogenic epochs. The separation of each stage ТМА on 2 stages is argued: purely ТМА and tectonic-metasomatical activating, which one are parted by a particular interim between formations rocks and ores.